The stabilizing system of the spine - Radziminska, Agnieszka; Weber-Rajek, Magdalena; Strączyńska, Agnieszka; Zukow, Walery (Journal of Education, Health and Sport, 2017)
The spatial orientation of the lumbar part of spine determines the position of central axis of the human skeleton, which in turn is closely related to the position of the pelvis. In a biomechanical aspect, the pelvis should be connected with the lumbar spine but also with the hip joints ( lumbo-pelvic-hip complex – LPH) . This area is intended to provide the body with the stability needed to carry the load with simultaneous maintaining the mobility required to perform locomotive functions. Stabilization means the maintenance of balance in both static and dynamic conditions, where the complex moves along a specific track. In the last decades of 20th and early 21st century there was a discussion whether stabilization of the LPH complex was more about the activation of deep muscles (local) or combination of deep and superficial muscles contraction (global). It is now known that both global and local muscles play an important role in stabilization. <span style="color: windowtext; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US">The stabilizing<span style="color: windowtext; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US"> system of the spine, which was introduced by Panjabi in 1992, works on the cooperation of those three systems: neural, which is the control system; muscular-fascial, which is the active system; osteoarticular - ligamentous, which creates a passive system. Hoffman and Gabel [22] proposed a new, extended theoretical model in which the new mobility system is placed beside the existing stability system and subsystems. Harmonious work of stability and mobility systems determines the quality of movement, but the malfunction of these systems affects other subsystems and thereby the quality of movement. The authors of this theoretical model suggest that both rehabilitation and mobility systems should be involved in rehabilitation exercises, with the movement being at a possible level but without pain and discomfort. LPH stabilization exercises are used in physiotherapeutic procedures in patients with pain and traumas, with stress urinary incontinence and in pregnant women.